(untitled) (Bangladesh Heart Journal, 2019)
Background: Limited contemporary data exist regarding the impact of SYNTAX score on procedural outcomes undergoing primary percutaneous coronary intervention(PCI) in acute STEMI patients. Objectives: To evaluate the significance of the SYNTAX score for predicting procedural outcome after primary PCI in patient with acute STEMI. Methods: This perspective observational study was conducted in the department of cardiology, National Institute of Cardiovascular Diseases, Dhaka, Bangladesh from September, 2015 to September, 2016. 42 patients with acute STEMI who underwent primary PCI were considered for the study. But 2 patients were excluded from the study due to failure of primary PCI. The patients were divided into two groups: Group I (low Syntax score d”22) and Group II (high Syntax score > 22). The Syntax score of all patients were calculated from an initial coronary angiogram before primary PCI. Procedural outcome was observed in between two groups. Results: Among study patients 57.5% were in SYNTAX score d”22 (Group I) and 42.5% were in SYNTAX score >22 (Group II). Among traditional cardiovascular risk factors diabetes was significantly more prevalent in the Group II than Group I ( 82.4% vs 34.8%, p Â 0.003). Angiographic profile revealed maximum (69.6% vs 17.6%) culprit lesion in LAD artery in Group I and maximum culprit lesion (64.7% vs 21.7%) in RCA in Group II, these were the statistically significant between Group I and Group II (P<0.05). The high SYNTAX score group had lower ejection fraction (47.8±5.1 vs. 54.4±4.3, p= 0.04), lower TIMI flow 3 rate (76.47% vs 91.3%, p= 0.03 ) greater rate of MACE (29.4% vs. 4.3%, p=0.041), lower procedural success rate ( 76.47 vs. 91.3%, p= 0.046) compared to the low SYNTAX score group. ROC curve showed 77% sensitivity and 32% specificity for SYNTAX score when cut off value was 22 Performance test of SYNTEX score in the setting of Primary PCI outcome showed positive predictive value 83%. Conclusions: SYNTAX score was an independent variable that can predict procedural outcomes Bangladesh Heart Journal 2019; 34(1) : 5-10